2018
DOI: 10.1242/jcs.207779
|View full text |Cite
|
Sign up to set email alerts
|

Rap1, Canoe and Mbt cooperate with Bazooka to promote zonula adherens assembly in the fly photoreceptor

Abstract: In Drosophila epithelial cells, apical exclusion of Bazooka (the Drosophila Par3 protein) defines the position of the zonula adherens (ZA), which demarcates the apical and lateral membrane and allows cells to assemble into sheets. Here, we show that the small GTPase Rap1, its effector Canoe (Cno) and the Cdc42 effector kinase Mushroom bodies tiny (Mbt), converge in regulating epithelial morphogenesis by coupling stabilization of the adherens junction (AJ) protein E-Cadherin and Bazooka retention at the ZA. Fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…Of special interest is the involvement of Mbt and PAK4 in Cadherin-mediated cell–cell adhesion ( Faure et al, 2005 ; Pütz, 2019 ; Schneeberger and Raabe, 2003 ; Selamat et al, 2015 ; Wallace et al, 2010 ; Walther et al, 2016 ). Together with Canoe (vertebrate AF6 or AFDN), Rap1 and Bazooka (Par3), Mbt is one of the key players remodeling the zonula adherens ( Walther et al, 2018 , 2016 ). It is conceivable that this network also influences synaptic contacts, as rat AF6 localizes at synapses ( Xie et al, 2008 ) and Rap1 is involved in the development and morphogenesis of the Drosophila neuromuscular junction ( Ou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of special interest is the involvement of Mbt and PAK4 in Cadherin-mediated cell–cell adhesion ( Faure et al, 2005 ; Pütz, 2019 ; Schneeberger and Raabe, 2003 ; Selamat et al, 2015 ; Wallace et al, 2010 ; Walther et al, 2016 ). Together with Canoe (vertebrate AF6 or AFDN), Rap1 and Bazooka (Par3), Mbt is one of the key players remodeling the zonula adherens ( Walther et al, 2018 , 2016 ). It is conceivable that this network also influences synaptic contacts, as rat AF6 localizes at synapses ( Xie et al, 2008 ) and Rap1 is involved in the development and morphogenesis of the Drosophila neuromuscular junction ( Ou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, as loss of Catenins prevents cell adhesion and therefore transmission of external and internal forces through the junctional network, we wanted to analyze further the role of AJs by modulating rather than abrogating AJ function. Strikingly, we found that overexpression of Afadin (Also known as Canoe, Cno) (Mandai et al, 2013;Bonello et al, 2018;Walther et al, 2018), an AJ regulator that co-localizes with β-cat to follicle cell junctions (Fig. S5B,B′), caused flattening of NCCs by stage 9 (Fig.…”
Section: Junctional Tension and Medial Myoii Levels Are Higher In Nccmentioning
confidence: 97%
“…Retention of Bazooka at the adherens junction plays a role in preventing the ectopic localization of the PAR complex and Ecad at the lateral membrane (Walther et al, 2016). Although the mechanisms underlying Mbt/PAK4 function during junction maturation are not fully understood, recent work in Drosophila has linked Mbt function during adherens junction maturation to that of the small GTPase Rap1 and its effector Canoe (Cno; afadin in humans), which binds to F-actin (Walther et al, 2018). The Rap1-Cno pathway also regulates Bazooka localization in the fly embryo during cellularization (Bonello et al, 2018), and Ecad trafficking in MDCK cells (Hogan et al, 2004).…”
Section: The Cdc42-pak4 Axis In Junction Maturationmentioning
confidence: 99%